Molecular imaging in management of colorectal metastases by the interventional oncologist. (31st December 2022) - Hunt, Stephen; Zandifar, Alireza; Alavi, Abass
Abstract: Interventional oncologists provide several effective treatment options for patients with metastatic colorectal cancer (mCRC), including embolization and ablation-based techniques. Molecular imaging methods such as positron emission tomography (PET) can play an important role in managing mCRC patients. In this review, we aim to highlight the role of molecular imaging in mCRC management by interventional oncologists including: initial staging and pretreatment planning; predicting molecular subtypes, prognosis, and treatment outcomes; intraprocedural guidance; and assessing treatment response and post-procedural monitoring.